Economic Potential of Ecuador’s Mining Sector and Intrinsic Stock Value Analysis of Companies Operating in Ecuador - Vaněk, Michal; Chrascina, Marek; Stejskal, David; Santiago Burbano Morillo, Danny (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2025)
Economic and social development are inextricably linked to commodities. The attractiveness of a given mining sector in a given country and its economic potential are reflected in the market values of specific mining companies. This study examines the economic potential of Ecuador’s mining sector and assesses in-vestment opportunities through intrinsic stock valuation. Recent political developments have created a favorable environment for large-scale foreign mining investment, attracting growing international interest. The study contributes to the existing literature by addressing a notable gap: the lack of quantitative assessments of Ecua-dor’s mining sector and the absence of stock-level valuation analyses specific to this geographic and sectoral context. Using Dividend Discount Models (DDM), Earnings Models (EM), and Cash Flow Models (CFM), it evaluates companies operating in or investing in Ecuador, a country positioned along the Andean mineral belt – one of the world’s richest geological zones. By applying established financial models, this research offers a structured approach for evaluating mining-related equity investments in emerging markets. The analysis identifies undervalued and overvalued stocks based on fundamental valuation metrics, with firms such as Dun-dee Precious Metals, Lundin Gold, and Anglo American demonstrating high investment potential, while BHP group and Silvercorp Metals appears overvalued. These findings are contextualized within broader commodity market dynamics, offering insights into risk-adjusted investment attractiveness.
Mining Science, Vol. 32, 2025, s. 135-154
Keywords: górnictwo; geologia; geoinżynieria; commodity markets; Ecuadorian mining sector; intrinsic stock value; valuation techniques and predictive models